'Partial' participation in Payments for Environmental Services (PES): Land enrolment and forest loss in the Mexican Lacandona Rainforest. (September 2019) - Izquierdo-Tort, Santiago; Ortiz-Rosas, Fiorella; Vázquez-Cisneros, Paola Angélica
Highlights: We study PES land selection and forest loss in the Lacandona Rainforest. We combine geospatial analysis with qualitative research among PES participants. Most people 'partially' participate in PES, i.e. enrol only some of their lands. Land decisions involve a complex cognitive mix of rational behaviour and heuristics. Land choices reflect opportunity costs and livelihood aspirations and constraints. Abstract: Payments for Environmental Services (PES) mushroomed since the late 1990s as a key strategy to curb forest loss and degradation. PES typically provide conditional incentives for the conservation of standing forests, often in short-term and renewable contracts. Although the topic of participation in PES has been covered extensively, there is a gap in the literature when it comes to a more comprehensive examination of how landholders make decisions about which lands to enrol in a PES programme. This paper investigates how people make PES-related land use decisions and how they manage enrolled and non-enrolled lands during their contracts. We build a framework rooted in social-ecological systems that accounts for the characteristics of resource users involved in PES, and the multiple motivations and decision-making processes related to land use. Our mixed-methods approach combines geospatial land distribution and forest cover loss analysis in a region of six communities in the Mexican Lacandona Rainforest, and in-depth qualitative research among three of these communities. Our geospatial analysis shows that compliance with PES on enrolled parcels may coevolve with extensive forest loss if people 'partially' participate in PES by enrolling only a fraction of their eligible lands. Our qualitative research shows that decisions about which lands to enrol in PES involve a complex cognitive mix, –combining rational behaviour, biases and heuristics–, reflecting a series of tensions between land opportunity costs, livelihood aspirations and constraints for expanding the agricultural frontier. Based on our findings, we discuss how a better conceptualisation of resource users involved in PES, and their land-related behaviour, enables a more complete understanding of the decision-making processes underlying enrolment outcomes, and we also discuss how our framework, methodology, and empirical evidence allows to better understand and evaluate PES effectiveness.